Cigarette flavours and design features available near schools before plain packaging implementation in Uruguay - Laura Llambi; Mauricio Minacapilli; Mary Barros; Carolina Parodi; Valentina Gonzalez Peluffo; Virginia Nuñez (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Background: The tobacco industry continually develops marketing strategies to reach potential new consumers. One of these strategies is marketing the cigarette itself through design appeals and flavours. Uruguay is the second country to implement plain packaging legislation for cigarettes in the Americas in 2020. This study aimed to explore flavouring and design features of tobacco products available near Uruguay schools immediately before the implementation of standardized plain package legislation, to monitor tobacco industry tactics. Methods: A fieldwork protocol was adapted from the one developed at Johns Hopkins University and implemented in fifteen neighbourhoods in Montevideo, Uruguay, across different socioeconomic areas. The protocol included surveying retailers near schools, purchasing tobacco, and coding per its characteristics. Results: Among the surveyed retailers, 86.67% sold flavoured cigarettes. Twenty-three unique tobacco products were purchased. Appealing design features were identified in 73.9% of the packs and 34.78% of the products were flavoured cigarettes. Flavoured cigarettes lacked the child protection warning in a greater proportion than non-flavoured ones. The most frequently found filter designs concerned the activation of flavour with capsule designs (33.3%) and features meant to imitate technological symbols that appeal to youth.  Conclusions: This study shows an increase in availability of flavoured cigarettes in Uruguay immediately before plain packaging implementation. In countries developing plain packaging legislation flavour proliferation and modification of design features must be monitored and addressed.